2022
DOI: 10.3389/fpubh.2022.857818
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Sodium Consumption in Mexico: A Strategy to Decrease the Morbidity and Mortality of Cardiovascular Diseases

Abstract: Hypertension (HTN) and cardiovascular diseases (CVD) are important public health problems in Mexico. High sodium intake is linked to high blood pressure and increased risk of developing CVD. International organizations suggest consuming <2 g of sodium/day; however, the Mexican population consumes amounts above what is recommended: 3.1 g/day. Although efforts have been made to mitigate this problem, interventions are needed to improve cardiovascular health. This policy brief offers a short review of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…La ingesta elevada de sodio, vinculada al riesgo cardiovascular, excede las recomendaciones de la OMS de menos de 2 g diarios en México y América Latina. 33,34,35 Sin embargo, en Perú, la mayoría de los alimentos vendidos y consumidos fuera de casa tienen un alto nivel de sodio. 35 El estudio de Carrillo reveló que el 95 % de estudiantes de ciencias de la salud asoció el exceso de sal con hipertensión; el 29 % con cálculos renales; solo el 6 % con otras enfermedades como cáncer, y el 47 % optaría por reducir la sal en su dieta.…”
Section: Discussionunclassified
“…La ingesta elevada de sodio, vinculada al riesgo cardiovascular, excede las recomendaciones de la OMS de menos de 2 g diarios en México y América Latina. 33,34,35 Sin embargo, en Perú, la mayoría de los alimentos vendidos y consumidos fuera de casa tienen un alto nivel de sodio. 35 El estudio de Carrillo reveló que el 95 % de estudiantes de ciencias de la salud asoció el exceso de sal con hipertensión; el 29 % con cálculos renales; solo el 6 % con otras enfermedades como cáncer, y el 47 % optaría por reducir la sal en su dieta.…”
Section: Discussionunclassified
“…Although this study did not measure the cost-effectiveness of reducing sodium intake, scientific evidence has shown that reducing sodium intake at the population level is one of the most cost-effective strategies to help reduce CVD risk [13,50]. Despite the fact that direct and indirect policy measures have been implemented in Mexico to reduce sodium consumption in the population (including front-of-package labelling, prohibiting salt shakers at the tables in restaurants, and sodium reduction in bakery products) [51][52][53], excessive sodium intake continues to represent an important risk factor for CVD in the country. In this regard, our study showed that reducing sodium intake, regardless of the policy scenario, could contribute to significantly reduce CVD mortality in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study did not measure the cost effectiveness of reducing sodium intake, scienti c evidence has shown that reducing sodium intake at the level is one of the most cost-effective strategies to help reduce CVD risk (12,40). Despite the fact that direct and indirect policy measures have been implemented in Mexico to reduce sodium consumption in the population (including front-of-package labelling, prohibiting salt shakers at the tables in restaurants, and sodium reduction in bakery products) (41)(42)(43), excessive sodium intake continues to represent an important risk factor for CVD in the country.…”
Section: Discussionmentioning
confidence: 99%